Entendendo as crenças em teorias da conspiração: contribuição dos traços de personalidade e valores humanos - Rezende, Alessandro Teixeira (2019)
This dissertation aimed to verify to what extent personality traits and human values explain beliefs in conspiracy theories. Four empirical studies were conducted. Study 1 aimed to map the meanings that individuals attribute to conspiracy theories. Participants were 383 university students from public institutions of João Pessoa-PB, with a mean age of 21 years (SD = 5.07). They answered a sociodemographic questionnaire and two open-ended questions. In summary, the results were congruent with international research in psychology, suggesting that conspiracy theories can be understood as an explanatory function for social reality events. Study 2 focused on the elaboration of the General Beliefs Conspiratorial Scale (GBCS). The items were created based both on the lexical structures previous mentioned in Study 1 and on the instruments available in the literature. Participants were 229 university students from a public institution of João Pessoa-PB, with a mean age of 21 years (SD = 4.50), who answered the initial version of GBCS-39 composed by 39 items and demographic questions. A Principal Component Analysis (varimax rotation) indicated a five-dimensional structure with acceptable indicators of reliability. Each dimension was composed by three items: Pharmaceutical Handling (α = 0.75), Global conspiracies (α = 0.80), Secret groups manipulation (α = 0.80), Concealment of contact with aliens (α = 0.92) and Information control (α = 0.60). The GBCS accounting for 55.4% of the total variance. Taking account the exploratory procedures applied in the previous study, the Study 3 aimed to confirm the factorial structure of the GBCS scale. Participants were 229 students from a public institution of João Pessoa-PB, with a mean age of 21 years (SD = 5.31), who answered the short form version of the GBCS scale and demographic questions. Alternative models were tested, however the bifator model (e.g., CFI = 0.96, TLI = 0.94, RMSEA = 0.06) presented better fit; in addition, the temporal stability of the scale evaluated over a period of thirty days revealed a high correlation value at the two application moments (r = 0.85). The Study 4 investigated the relationship between human values, personality traits and beliefs in conspiracy theories. Participants were 205 university students from a public institution in the city of João Pessoa- PB, with a mean age of 21 years (SD = 5.14), who answered the GBCS-15, the Big Five Inventory, the Basic Values Survey (BVS) and demographic questions. The results indicated that personality traits and human values predicted the beliefs in conspiracy theories. In addition, the structural equation model presented satisfactory adjustment indicators (e.g., CFI = 0,95, TLI = 0,90). It is estimated that the proposed objectives were reached by constructing a self-report measure to evaluate beliefs in conspiracy theories, presenting preliminary evidence of its factorial validity and internal consistency, as well as increasing the understanding of theories conspiracy on the basis of the relations it establishes with other constructs.